I am a witch's cat - Muncaster, Harriet (New York : Harper, 2014)
A "special witch's cat" is certain her mother is a witch because she keeps special potions in the bathroom, grows magical herbs in her garden, and whirls her broomstick around the room once a week.
Keywords: Mothers and daughters; Imagination; Witches; Cats; Picture book